Peran Orang Tua dalam Meningkatkan Kemampuan Literasi Baca Tulis Anak di Sekolah Dasar Kabupaten Landak - Kristina Natasari; Dahniar Th. Musa; Reiki Nauli Harahap; Herlan Herlan; Marini Marini (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to analyze the role of parents in improving children’s reading and writing literacy skills at SDN 08 Kurnia, Semedang Village, Kuala Behe Subdistrict, Landak Regency. This study employs a descriptive qualitative approach, with data collected through in-depth interviews, observation, and documentation. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions based on the research findings. The results indicate that the role of parents in improving children’s reading and writing literacy skills in Semedang Village has not yet been fully realized. In terms of education, parental involvement remains limited due to a lack of understanding regarding effective learning support. In terms of motivation, parents have not consistently encouraged learning activities within the family. In terms of facilitation, the family’s economic constraints are one of the factors preventing the provision of literacy support materials, such as reading books and learning media. In terms of guidance, time constraints due to work demands have prevented the intensity of support for children’s learning activities from reaching its full potential. This situation is influenced by several factors, including internal factors such as parents’ educational backgrounds and family economic conditions, as well as external factors such as a surrounding environment that does not yet support a culture of literacy, the influence of peers, and the use of digital media. These factors have prevented the establishment of sustainable literacy activities within the family environment.